2021
DOI: 10.14513/actatechjaur.00611
|View full text |Cite
|
Sign up to set email alerts
|

Review of the effect of sand on the behavior of expansive clayey soils

Abstract: Clayey soils often showed undesirable engineering behavior such as low bearing capacity, swelling and shrinkage characteristics. However, chemical improvement, thermal improvement and improvement by additives like lime, cement and sand offer an efficient technique to overcome the problems resulting from Expansive soils. This paper presents a review of the swelling behavior of sand-clay mixtures as well as the effect of sand on the physical and mechanical characteristics of expansive soils. Results highlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Balancing the sand fraction is critical in engineering applications because it improves soil performance and reduces the negative impacts of cracking in expansive soil [19]. The addition of sand to expansive soils has been extensively investigated by many researchers to determine its effect on the soil parameters [10,[20][21][22][23][24][25][26]. Previous studies have confirmed that increasing the percentage of sand increases the unconfined compressive strength (UCS) of expansive soils.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%
“…Balancing the sand fraction is critical in engineering applications because it improves soil performance and reduces the negative impacts of cracking in expansive soil [19]. The addition of sand to expansive soils has been extensively investigated by many researchers to determine its effect on the soil parameters [10,[20][21][22][23][24][25][26]. Previous studies have confirmed that increasing the percentage of sand increases the unconfined compressive strength (UCS) of expansive soils.…”
Section: Sand As An Additive Materials and Its Impact On Soil Parametersmentioning
confidence: 99%
“…Uji pengembangan dilakukan untuk membandingkan dengan nilai awalnya untuk meneliti variasi perilaku pengembangan tanah ekspansif pada kedalaman yang berbeda setelah pengujian model selesai (She dkk, 2019). Beberapa cara untuk mengurangi tingkat aktivitas suatu mineral dalam ekspansive soil yaitu seperti penelitian yang dilakukan oleh (Alnmr & Ray, 2021), penelitian tersebut menyajikan tinjauan perilaku pengembangan campuran pasir-lempung serta pengaruh pasir terhadap karakteristik fisik dan mekanik tanah ekspansif.…”
Section: Hasil Dan Pembahasanunclassified
“…The design of the targeted model is illustrated in Figs. 14. As for the soil reinforced with CSV, 20 columns were used; each column consists of 20 cm in diameters and 10 m in length, separated from each other by 1m.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…For this reason, three percentages (25%, 50% and 75%) of soft soil contents in CSV materials are studied. Authors [10][11][12][13][14], have noticed that the added cement triggered a sudden fall in the residual strength. To tackle this problem, PP fiber is purposefully used, as it can greatly enhance the residual strength [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%